The development of penguinpox virus (PEPV) as a vaccine vector : transfer vector construction and rescue of virus growth in rabbit kidney cells (RK-13) by vaccinia virus K1 - Hu, Nai-Chung (Division of Virology, 2014)
Includes bibliographical references (leaves 131-137).